ALTERNATIF KEBIJAKAN PERILAKU PENGGUNAAN KONDOM UNTUK PENCEGAHAN HIV PADA PEKERJA SEKS WARIA DI LOKALISASI GOR KOTA BEKASI TAHUN 2014 - Simamora, Rotua Suriany (Jurnal Ilmiah Widya, 2014)
The number HIV prevalence at transvestite prostitutes kept growing from year to year. It was 23, 2% in 2011. The on going up level of HIV prevalence in this population was caused of the inconsistence of using condoms in sexual activities. The objectives of this research are: (1) to discuss the HIV prevalence (2) try to find out the alternative to give the Behavior policy alternative which could be used to increase the use of condoms in preventing HIV at transvestite prostitutes in the sport center of Bekasi in 2014. This study used a confirmatory qualitative as through further interviews, observations and document studies. There were 8 informants as samples chosen through a purposive sampling that consisted of the transvestite prostitutes, the head of health service and the coordinator of non governmental organization. The results show that (1) the factors on individual levels (internal) which consisted of knowledge, motivation, and readiness to change behavior and willingness to support the use of using condoms even though it was still inconsistent. (2) Factors of interpersonal levels consisted of the influence of unchanging partner, friends of the same age, and seniors and clients who generally supported and not to support the behavior of using condoms in every sexual intercourse. (3) Factors of public policy level especially the public policy in Bekasi was still weak and found to support as well as hamper the behavior of using condoms. (4) The content of current policy was still relative and only recognized some of the important aspects in preventing and handling HIV/AIDS. (5) The alternative policy as TOR was the suggestion of improvement program, activities, budget for prevention and handling HIV/AIDS in Bekasi.